PENGARUH ELASTIC BAND EXERCISE TERHADAP LANSIA DENGAN GANGGUAN KESEIMBANGAN (Studi Kuasi Eksperimen : Pada Lansia Di PSTW Budi Mulya I Tahun 2022) - Ratu Karel Lina; Sri Yani; R Trioclarise (Jurnal Fisioterapi dan Kesehatan Indonesia, 2023)
Aging or increasing age is a condition that must occur in human life. Balance disorders are one of the problems that occur due to physiological changes in the elderly. One strategy to improve balance is with physiotherapy modalities. Various interventions that can be given physiotherapy to improve balance, one of which is elastic band exercise. The purpose of this study was to determine the effect of elastic band exercise on the elderly with balance disorders. Methodology: Quasi experimental research design using Two-group pretest-posttest design. The research population is all the elderly in PSTW Cipayung. The results of the sample count were 15 people per group, a total of 30 people. The independent variable in this study was the Elastic Band Exercise intervention. The dependent variable is the balance of the elderly. This research will be conducted in April – September 2022. Data collection uses a balance assessment instrument and then the Elastic Band Exercise intervention. Data analysis was carried out univariate and bivariate. The results showed that there were 2 sample groups with the same number, namely the intervention group as many as 15 people (50.0%), and the control group as many as 15 people (50.0%). The results of the bivariate analysis showed that there was a significant difference in the average balance in the elderly between before and after in the intervention group (p = 0.0001), there was a significant difference in the average balance in the elderly between before and after (p = 0.028) in the control group. , and there was a significant difference in the average elderly balance between the intervention group and the control group (p = 0.0001). Research suggestions so that the elderly can practice Elastic Band Exercise regularly and regularly, relax by keeping the heart and mind so as not to stress.